Social and religious factors in pilgrimages on the Way of Saint James - Omelan, Aneta Anna; Furgała-Selezniow, Grażyna; Jankun-Woźnicka, Małgorzata (Quaestiones Geographicae, 2025)
This study examines the evolution of the Camino de Santiago into a hybrid of religious pilgrimage and spiritual tourism. Through statistical analysis and interviews with members of the Camino de Santiago Polska Facebook group, the research provides insights into the evolving nature of this historic route. Analysing data from 2003 to 2024, it reveals a significant increase in the number of international pilgrims. While religious motivations persist, non-religious and mixed motivations increase, especially after the pandemic. The study concludes that the Camino de Santiago represents a diverse form of tourism, blending religious and secular motivations, with implications for sustainable tourism development.